Tumour heterogeneity and metastasis at single-cell resolution. Issue 12 (December 2018) - Lawson, Devon; Kessenbrock, Kai; Davis, Ryan; Pervolarakis, Nicholas; Werb, Zena
Abstract Tumours comprise a heterogeneous collection of cells with distinct genetic and phenotypic properties that can differentially promote progression, metastasis and drug resistance. Emerging single-cell technologies provide a new opportunity to profile individual cells within tumours and investigate what roles they play in these processes. This Review discusses key technological considerations for single-cell studies in cancer, new findings using single-cell technologies and critical open questions for future applications. Lawson et al. review recent advances in single-cell technologies and discuss in detail how they can be leveraged to understand tumour heterogeneity and metastasis.